Integrated 16S and metabolomics revealed the mechanism of drought resistance and nitrogen uptake in rice at the heading stage under different nitrogen levels - Sun, Changhui; Wang, Runnan; Tang, Guoping; Cai, Shuo; Shi, Hong; Liu, Fangping; Xie, Hengwang; Zhu, Jinyan; Xiong, Qiangqiang (Frontiers in Plant Science, 2023)
The normal operation of agricultural production worldwide has been strongly affected by the frequent occurrence of drought. Rice rhizosphere microorganisms have been significantly affected by drought stress. In this study, a barrel planting method was adopted. At the heading stage, the rice was treated with no drought and drought stress, and the following nitrogen (N) levels were utilized: low N, normal N (control), and high N. The N uptake and utilization of rice were analysed with different types of water and N applications. Untargeted metabolomics and 16S rRNA gene sequencing technology were used to study the changes in microorganisms in roots and differential metabolites (DMs) in rhizosphere soil. The results showed that under the same N application rate, the dry matter mass, N content and N accumulation in rice plants increased to different degrees under drought stress. The root soluble protein, nitrate reductase and soil urease activities were improved to a certain extent compared with that of the no-drought treatment. Proteobacteria, Bacteroidota, Nitrospiota and Zixibacteria were the dominant flora related to N absorption. A total of 184 DMs (98 upregulated and 86 downregulated) were identified between LN (low N with no drought) and NN (normal N with no drought); 139 DMs (83 upregulated and 56 downregulated) were identified between HN (high N with no drought) and NN; 166 DMs (103 upregulated and 63 downregulated) were identified between LND (low N with drought stress) and NND (normal N with drought stress); and 124 DMs (71 upregulated and 53 downregulated) were identified between HND (high N with drought stress) and NND. Fatty acyl was the metabolite with the highest proportion. KEGG analysis showed that energy metabolism pathways, such as D-alanine metabolism and the phosphotransferase system (PTS), were enriched. Overall, the study provides a hypothetical basis for improving the drought resistance and N utilization efficiency of rice.